Upaya Paguyuban Manunggal Karso (PMK) dalam Mewujudkan Lingkungan Hidup Bersih dan Sehat di Bantaran Sungai Gajah Wong Kelurahan Baciro, Kecamatan Gondokusuman, Kota Yogyakarta - Anisak Nur Latifah (SOSIO PROGRESIF | Media Pemikiran Studi Pembangunan Sosial, 2021)
Yogyakarta City is one of the big cities that cannot be separated from environmental problems, especially in the riverbank areas. Generally, the main function of river is to collected rainwater in an area and drain it into the sea (Mori, 1993: 169-170). However, the rivers in Yogyakarta has undergone a shift in function, from the main function of the river to drain rainwater in anticipation of flooding, currently the area around the river was used as a place to live which threaten the sustainability of the river itself. One of the rivers that crosses the city of Yogyakarta is the Gajah Wong River, now the river has undergone a shift in function as a residential area. So in this case the Gajah Wong river activists who called the Paguyuban Manunggal Karso is one of attempt to preserve the river and change the development of riverbank communities to be aware of the dangers that threaten every day. Efforts that made by Paguyuban Manunggal Karso include mutual cooperation to build inspection roads, conserve river and embodied the M3K programme (Munggah, Mundur, Madhep Kali) in the riverbank area.